Hidden children of the Holocaust: Belgian nuns and their daring rescue of young Jews from the Nazis - Vromen, Suzanne (Oxford University Press, 2008)
In Belgium in the summer of 1942, when the Nazis began the brutal roundup of Jewish families, parents searched desperately for safe havens for their children. This book tells the stories of children who found haven in Roman Catholic convents and orphanages, and of the women who sheltered them